Comprehensive meiotic segregation analysis of a 4-breakpoint t(1;3;6) complex chromosome rearrangement using single sperm array comparative genomic hybridization and FISH - Hornak, Miroslav; Vozdova, Miluse; Musilova, Petra; Prinosilova, Petra; Oracova, Eva; Linkova, Vlasta; Vesela, Katerina; Rubes, Jiri (Reproductive biomedicine online, 2014)
Complex chromosomal rearrangements (CCR) represent rare structural chromosome abnormalities frequently associated with infertility. In this study, meiotic segregation in spermatozoa of an infertile normospermic carrier of a 4-breakpoint t(1;3;6) CCR was analysed. A newly developed array comparative genomic hybridization protocol was used, and all chromosomes in 50 single sperm cells were simultaneously examined. Three-colour FISH was used to analyse chromosome segregation in 1557 other single sperm cells. It was also used to measure an interchromosomal effect; sperm chromatin structure assay was used to measure chromatin integrity. A high-frequency of unbalanced spermatozoa (84%) was observed, mostly arising from the 3:3 symmetrical segregation mode. Array comparative genomic hybridization was used to detect additional aneuploidies in two out of 50 spermatozoa (4%) in chromosomes not involved in the complex chromosome rearrangement. Significantly increased rates of diploidy and XY disomy were found in the CCR carrier compared with the control group (P < 0.001). Defective condensation of sperm chromatin was also found in 22.7% of spermatozoa by sperm chromatin structure assay. The results indicate that the infertility in the man with CCR and normal spermatozoa was caused by a production of chromosomally unbalanced, XY disomic and diploid spermatozoa and spermatozoa with defective chromatin condensation.
Keywords: array CGH; segregace chromozomů; Meiotic Prophase I; Adult; Disorder of Sex Development, 46,XY; male infertility; genová přestavba; Chromosome Breakpoints; Czech Republic; mužská infertilita; translokace genetická; Translocation, Genetic; Gene Rearrangement; sperm aneuploidy; spermie; heterozygot; lidé; meiotic segregation; Česká republika; Heterozygote; body zlomu chromozomu; mužské pohlaví; In Situ Hybridization, Fluorescence; profáze meiózy I; dospělí; Chromosome Segregation; analýza jednotlivých buněk; Humans; Infertility, Male; poruchy sexuálního vývoje s karyotypem 46, XY; hybridizace in situ fluorescenční; complex chromosome rearrangement; interchromosomal effect; Spermatozoa; Male; Single-Cell Analysis; srovnávací genomová hybridizace; Comparative Genomic Hybridization